Polymorphism in Crystalline Microfibers of Achiral Octithiophene: The Effect on Charge Transport, Supramolecular Chirality and Optical Properties. (22nd May 2014) - Di Maria, Francesca; Fabiano, Eduardo; Gentili, Denis; Biasiucci, Mariano; Salzillo, Tommaso; Bergamini, Giacomo; Gazzano, Massimo; Zanelli, Alberto; Brillante, Aldo; Cavallini, Massimiliano; Della Sala, Fabio; Gigli, Giuseppe; et al.
<x xml:space="preserve">Abstract</x> Polymorphic crystalline microfibers from an achiral octithiophene with one S‐hexyl substituent per ring are separately and reproducibly grown with the same characteristics on various solid surfaces, including the interdigitated electrodes/SiO2 surface of a bottomcontact field‐effect transistor. The arrangement of the same molecule in two diverse supramolecular structures leads to markedly different electronic, optical, and charge mobility properties. The microfibers—straight and yellow emitting or helical and red emitting—exhibit p‐type charge transport characteristics, with the yellow ones showing a charge mobility and on/off current ratio of one and three orders of magnitude, respectively, greater than the red ones. Both forms show circular dichroism signals with significant differences from one form to the other. DFT calculations show that the octithiophene exists in two different quasi‐equienergetic conformations aggregating with diverse orientations of the substituents. This result suggests that the observed polymorphism is conformational in nature. The self‐assembly, driven by sulfur–sulfur non‐bonding interactions, amplifies the small property differences between conformers, leading to quite different bulk properties.